Determinants of the increase in violence against women by intimate partner during the covid-19 pandemic: a brief integrative review (Brazilian Journal of Health Research, 2023)
Introduction: Confinement and social distancing promoted by the covid-19 pandemic boosted indicators of intimate partner violence (IPV) against women. Objective: To identify determinants of the increase in IPV against women during the mandatory home quarantine imposed by the covid-19 pandemic. Methods: Integrative literature review conducted in the PubMed/MEDLINE database in January 2023. “Violence against women” AND “Coronavirus infections” AND “Intimate partner violence” were used as search terms. 49 studies were found, 16 were included according to the eligibility criteria: articles in Portuguese/English that addressed IPV during the covid-19 pandemic. Results: Socioeconomic factors, mental health issues and substance use disorders were cited as determinants of the increase in IPV during the pandemic. This increase during the period was associated with the mandatory stay of women with their aggressors in their homes, as seen in data from some countries: Nigeria, Tunisia (14.8%), Democratic Republic of Congo (11.7%), Ethiopia (42.19%), Kenya (17.5%), India (18.1%), Germany, Czech Republic, Italy, Spain, and Chile. Comparing statistics between April 2019 and 2020, the WHO found a five-fold increase in online searches for hotlines to support and prevent cases of IPV. Conclusion: Behavioral changes, individual and socio-cultural factors were related to the increase in IPV against women during the restrictive impositions resulting from covid-19.
Keywords: Violence against women; Coronavirus infections; Intimate partner violence